Metal Injection Moulding Parameters Optimization and Interaction Study Using Taguchi Method - Tan, Koon Tatt; Muhamad, Norhamidi; Che Haron, Che Hassan; Sulong, Abu Bakar (International Journal of Integrated Engineering, 2020)
In this study, the Taguchi method is used to find the optimal moulding parameters for the metal injection moulding (MIM) feedstocks. Parameters optimised are injection temperature (factor A), mould temperature (factor B), injection pressure (factor C) and flow rate (factor D). Feedstocks used were water atomised stainless steel powder with a solid loading of 62 %Vol and the multicomponent binder consisting  PEG, PMMA and strearic acid. Green defects and green density were considered as quality characteristics (response) and optimised by using Taguchiâ€™s L81 (340) orthogonal array. Green defects evaluated using parameter design for discrete data technique while green densities were measured according to the MPIF standard 42. The signal-to-noise (S/N) ratio and analysis of variance (ANOVA) are employed to investigate the quality characteristics. The analysis results show that the mould temperature (factor B) is the most significant factor affecting the quality characteristic. The optimal conditions for the green defects and green density are A1B2C0D1 and A2B2C1D0 respectively. The influences of the two-factor interactions and three-factor interactions cannot be neglected.